The Effect of Social Commerce Features and Electronic Word of Mouth on Consumer Purchase Intentions for Local Skincare Products in Central Java - Erwin Erwin; Dila Padila Nurhasanah; Rival Pahrijal (West Science Social and Humanities Studies, 2026)
The rapid growth of social media-based commerce has significantly influenced consumer behavior, particularly in the skincare industry, where digital interaction and consumer-generated information play important roles in purchasing decisions. This study aims to examine the effect of social commerce features and electronic word of mouth (e-WOM) on consumers’ purchase intentions for local skincare products in Central Java. This research employed a quantitative approach using a survey method involving 150 respondents who had experience purchasing or using local skincare products. Data were collected through a structured questionnaire measured using a five-point Likert scale and analyzed using Statistical Package for the Social Sciences (SPSS) version 25. The analytical techniques included validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, t-test, F-test, and coefficient of determination analysis. The results indicate that social commerce features have a positive and significant effect on purchase intention. Furthermore, electronic word of mouth also has a positive and significant effect on purchase intention. The simultaneous test confirms that social commerce features and e-WOM significantly influence purchase intention, with an Adjusted R² value of 0.510, indicating that both variables explain 51.0% of consumer purchase intention variation. These findings demonstrate that interactive digital features and positive consumer recommendations are essential factors in strengthening consumer confidence toward local skincare products. This study provides practical implications for local skincare businesses to optimize social commerce strategies and encourage positive electronic word-of-mouth to improve competitiveness in the digital marketplace.